2019
DOI: 10.1111/all.14091
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary IL‐33 orchestrates innate immune cells to mediate respiratory syncytial virus‐evoked airway hyperreactivity and eosinophilia

Abstract: Background: Respiratory syncytial virus (RSV) infection is epidemiologically linked to asthma. During RSV infection, IL-33 is elevated and promotes immune cell activation, leading to the development of asthma. However, which immune cells are responsible for triggering airway hyperreactivity (AHR), inflammation and eosinophilia remained to be clarified. We aimed to elucidate the individual roles of IL-33-activated innate immune cells, including ILC2s and ST2 + myeloid cells, in RSV infection-triggered pathophys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 52 publications
0
47
0
Order By: Relevance
“…In addition, the recruitment of ILC2s induced by vascular cell adhesion molecule 1 (VCAM‐1) in the endothelial cells of the lung depends on the receptor for advanced glycation end products (RAGE) 54‐56 . Stimulations of mice with recombinant IL‐33 resulted in blood eosinophilia, and increased serum levels of IgE, IgA, IL‐5, IL‐13, and splenomegaly, while anti–IL‐33 treatment significantly reduced nose‐scratching events, ameliorated nasal cavity eosinophilia, and downregulated serum IgE levels in the murine model of AR 57 …”
Section: Epithelium‐derived Il‐33mentioning
confidence: 99%
“…In addition, the recruitment of ILC2s induced by vascular cell adhesion molecule 1 (VCAM‐1) in the endothelial cells of the lung depends on the receptor for advanced glycation end products (RAGE) 54‐56 . Stimulations of mice with recombinant IL‐33 resulted in blood eosinophilia, and increased serum levels of IgE, IgA, IL‐5, IL‐13, and splenomegaly, while anti–IL‐33 treatment significantly reduced nose‐scratching events, ameliorated nasal cavity eosinophilia, and downregulated serum IgE levels in the murine model of AR 57 …”
Section: Epithelium‐derived Il‐33mentioning
confidence: 99%
“…The disease caused by hRSV is characterized mainly by the infiltration of eosinophils and neutrophils into the airways. An increase infiltration of neutrophils can contribute to lung damage (210)(211)(212). Even though CD8 + T cells are key in the clearance of the virus, it has been reported that the depletion of the CD4 + and CD8 + T cells in mice decreased the severity of the illness (213)(214)(215).…”
Section: Human Respiratory Syncytial Virusmentioning
confidence: 99%
“…Finally, IFN-I is not the only modulator of CD5 + nBreg function. IL-33, an alarmin that belongs to the IL-1 family, is rapidly secreted following RSV exposure in neonates and contributes to the promotion of type-2 responses by promoting IL-13 and IL-5 production by ILC2 [13,45]. Recently, the importance of ILC2 in shaping the immune response early during RSV infection has been revealed in infants [46].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the importance of ILC2 in shaping the immune response early during RSV infection has been revealed in infants [46]. AMs are one of the source of IL-33 upon RSV infection [45,47,48], and it was shown that deletion of IL-33 production by myeloid cells strongly affects IL-5 secretion and eosinophil recruitment upon RSV infection [45]. Furthermore, IL-33 treatment promotes IL-10 production by B-cells in adult mice, thus protecting these mice from induction of inflammatory bowel disease [49].…”
Section: Discussionmentioning
confidence: 99%